Efficacité Technique des Petits Producteurs du Maïs au Bénin - Aminou, Fawaz A. Adéchinan (European Scientific Journal, ESJ, 2018)
This study examines how small maize farmers allocate their production inputs and identifies the elements that characterize efficient farms. A Cobb Douglas stochastic frontier approach is used to estimate farm level technical efficiency of maize farmers. Average technical efficiency of sampled farms was estimated to be 65.40% with a minimum of 20.47% and a maximum of 93.46%. The study further showed that the farmers’ sex, the use of improved seeds, the maize selling price, the non-farm income, the contact with an NGO, the access to credit and the production area played a positive and significant role in improving technical efficiency. The results imply that government can save resources used in extension services and focus on its improved seed distribution policy. Also, imperfections in the labor/capital market contribute to the low efficiency of farm households.